Alula Pankhurst - Francois Piguet (eds.): Moving People in Ethiopia. Development, Displacement and the State (Aethiopica, 2010)
Review
Keywords: Development; Displacement; State Politics; Anthropology; History; Politics; Case Studies; Statistics